Value Creation in Mergers and Acquisitions ─ Evidence from UK in 2013-2018 - Lei, Lei (2018)
Mergers and acquisitions (M&A) are always a hot topic that draws lots of attention on the capital market. Some transactions are successful, and both the shareholders in the acquiring firm and the target firm gain significantly from the transaction. However, in some transactions, only the shareholder in target firms gain, while the acquiring firm’s shareholder bares significant losses. In this study, the short-term performance of the UK acquiring firms is evaluated to find out the critical factors that may have significant effects on the value creation in M&A transaction. Three factors are proposed in this study (the type of payment, type of target firm and type of industry), with hypothesis related to them to investigate their impacts on the performance of acquiring firm. Followed by the majority of previous researches, standard event study methodology is applied in this research, and both five-day and three-day event windows are involved. The research also uses cross-sectional multivariate analysis to assess the combined effect of the three proposed factors. Based on 222 UK M&A transactions between 2013 and 2018. The main findings in this research are: in the short-term, cash payment method and private target firms have significantly positive impacts on the performance of acquiring firms. However, the hypothesis that UK acquiring firms involving in M&A transaction in non-financial industries performs better than those involved in financial industries is not well supported by the results. Additionally, recommendations throughout the M&A transaction such as due diligence and integration are proposed aiming to achieve more synergies, improve M&A efficiency and increase shareholder wealth.